2017
DOI: 10.3390/ijerph14050500
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Anti-Angiotensin II Type-1 Receptor Antibodies Adversely Affect Kidney Graft Outcomes

Abstract: The aim of this study was to determine whether anti-angiotensin type 1 receptor antibodies (AT1R-Abs) are related to acute rejection (AR) and kidney graft failure in renal transplantation. We searched electronic databases including MEDLINE, EMBASE, and the ISI Web of Science databases for all studies on the association between anti-angiotensin type 1 receptor antibodies and kidney allograft outcomes updated to November 2016. Reference lists from included articles were also reviewed. The pooled relative risks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We report here a strong and independent association between pre-transplant AT 1 R-Ab and ABMR h DSA pos development. AT 1 R can be found in several cell types such as vascular endothelial cells and binds to angiotensin II (39,47). First report linking AT 1 R-Ab and kidney allograft rejection suggested a potential relationship between AT 1 R agonistic antibodies and vascular injury (19,39).…”
Section: Discussionmentioning
confidence: 99%
“…We report here a strong and independent association between pre-transplant AT 1 R-Ab and ABMR h DSA pos development. AT 1 R can be found in several cell types such as vascular endothelial cells and binds to angiotensin II (39,47). First report linking AT 1 R-Ab and kidney allograft rejection suggested a potential relationship between AT 1 R agonistic antibodies and vascular injury (19,39).…”
Section: Discussionmentioning
confidence: 99%
“…Since the original paper describing AT1R-Ab in patients with acute AMR and hypertension, 8 multiple studies9, 16, 17, 33, 34, 35, 36, 37, 38, 39, 40 have indicated an association between AT1R-Ab with vascular inflammation and poor clinical outcomes. Studies with longitudinal measurements of AT1R-Ab9, 16, 36 remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis found a significant effect of AT1R‐Abs on the allograft outcome, without considering neither the threshold of AT1R‐Ab positivity nor the HLA‐Ab detection technology. A new meta‐analysis considering our new study could be interesting .…”
Section: Discussionmentioning
confidence: 99%
“…Dragun et al [8,13] have shown for the first time their involvement in patients presenting acute rejection episodes (ARE) with severe hypertensive crisis. Since this first observation, the correlation of anti-AT1R antibodies and acute rejection and/or graft failure has become more debated in kidney transplantation sometimes due to a lack of power of studies [15][16][17][18][19][20][21][22][23][24]. In 2013, we showed on a large monocentric cohort (n = 599) of French kidney recipients that patients who displayed a pretransplant AT1R-Ab level above 10 U/ml had higher risk of acute rejection episodes within the first month following transplantation and graft failure beyond 3 years post-transplantation [25,26].…”
Section: Introductionmentioning
confidence: 99%